PERAN GURU PENDIDIKAN ANAK USIA DINI DI YAYASAN SMART HOME TK ISLAM IMPIAN KELURAHAN BANGKALA KECAMATAN MANGGALA KOTA MAKASSAR - Nurdin, Wafiyyah Raffifa; Latang, Latang; Suardi, Suardi (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2023)
This study aims to determine the role of early childhood education teachers at the Smart Home Islamic Dream Kindergarten Foundation, Bangkala Village, Manggala District, Makassar City. This research is a qualitative research with a case study type of research, the informants in this study were tutors, the head of the Islamic Dream Kindergarten and the parents of the students. Data collection was carried out by interview, observation, and documentation techniques. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. Triangulation is used through triangulation of sources and methods. The results of the study show that the role of early childhood education teachers in Yayaysan Smart Home Islamic Dream Kindergarten, Bangkala Village, Manggala District, Makassar City, is specific to three things, namely the role of a mediator, the role of a facilitator, and the role of a motivator. The role of the teacher as a mediator is not only to know various educational media but the teacher also becomes an intermediary in the learning process. The role of the teacher as a facilitator who provides facilities and infrastructure to students free of charge in optimizing the learning process and providing learning tools. Then, the role of the teacher as a motivator is very important, where the teacher can move the classroom by using learning methods that suit the characteristics of their students.